Leigh Syndrome and the Mitochondrial m.13513G>A Mutation: Expanding the Clinical Spectrum. (November 2013) - Monlleo-Neila, Laura; Toro, Mireia del; Bornstein, Belen; Garcia-Arumi, Elena; Sarrias, Axel; Roig-Quilis, Manuel; Munell, Francina
The mitochondrial DNA m.13513G>A mutation in the ND5 subunit gene is a frequent cause of Leigh syndrome. Patients harboring this mutation typically present with ptosis and cardiac conduction abnormalities, particularly Wolff-Parkinson-White syndrome, and have a late clinical onset, which contrasts with the typical infantile form. The authors describe a patient presenting with intrauterine growth retardation and visual impairment at 3 months of age, followed by infantile spasms, severe gastrointestinal dysmotility, and neurological regression. The patient had hyperlactacidemia and bilateral basal ganglia and brainstem lesions on MRI. Although he did not present cardiac conduction abnormalities, his mother had been diagnosed with Wolff-Parkinson-White syndrome. The m.13513G>A mutation was found in the patient's muscle and in several tissues of his mother. The present results expand the phenotype of Leigh syndrome associated with the m.13513G>A mutation, which should be suspected in patients with early-onset mitochondrial encephalopathy with infantile spasms or prominent gastrointestinal smooth muscle involvement.